Systematic review on the rational use of amniotic membrane allografts in diabetic foot ulcer treatment - Kasun Lakmal; Oshan Basnayake; D. Hettiarachchi (BMC Surgery, 2021)
Abstract Background Diabetic foot ulcer is a complication with multiple aetiological factors which has a significant impact to patients’ lives and costs to the healthcare system. The potential of human amniotic membrane to act as an allograft has been studied in relation to this condition. Aim of this study is to evaluate the current scientific evidence on its effectiveness in healing diabetic foot ulcers. Methods Pubmed, Cochrane library, and Google scholar were searched using the search terms, “Amnion” OR “Placenta” AND “Diabetic foot”. (MeSH terms) in the title or the abstract field from 1st of January 2000 to 30th March 2020. The quality of published reports was assessed using standard methods. We searched for experimental and observational studies in terms of randomized control trials, prospective cohort, retrospective cohort studies and case series. Results When searched with Mesh terms, 12 citations in PubMed, 22 citations in Cochrane library and 30 in other data bases were found. After screening the studies and their reference lists, 12 studies met the inclusion criteria and the others were excluded. There were 8 randomized control trials (RCTs), 2 prospective studies and 2 retrospective studies employing different preparation methods of the amniotic membranes. A wide variation in study end points were noted. Majority of the RCTs (n = 7) were concluded with significantly higher wound closure rate compared to the conventional treatment groups. In prospective and retrospective studies, it was shown that large chronic ulcers which were resistant to closure with standard therapy achieved wound closure with amniotic membrane allografts. A meta-analysis could not be performed due to study heterogeneity, and publication bias was not assessed due to the small number of available studies which was not sufficient for accurate comparison. Conclusion Even though, the studies had some inherent heterogeneity due to different preparation methods, different study end points and outcome measurements. According to our review the current studies using amniotic membrane allografts give reliable evidence of reduction in healing time over conventional methods.